1994
DOI: 10.1177/0022002794038001009
|View full text |Cite
|
Sign up to set email alerts
|

Economic Growth and Defense Spending in Developing Countries

Abstract: This article investigates the causal relationship between economic growth and defense spending in 77 developing countries. The study employs Granger-causality tests using annual time series data for each of the 77 countries to analyse the presence and direction of causality between the two variables. The results indicate that the relationship between economic growth and defense spending cannot be generalized across countries. It may depend, among other things on the sample period of study and the level of soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
6

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 5 publications
2
23
0
6
Order By: Relevance
“…This result is in line with the findings of others (Chowdhury, 1991;Landu, 1993;Kusi, 1994;Al-Yousif, 2002;Chang et al, 2014;Pan et al, 2014), who have concluded that military expenditure depends on a number of factors including: the nature of the expenditure; the prevailing circumstances; and the concurrent government policies.…”
Section: Policy Implicationssupporting
confidence: 90%
“…This result is in line with the findings of others (Chowdhury, 1991;Landu, 1993;Kusi, 1994;Al-Yousif, 2002;Chang et al, 2014;Pan et al, 2014), who have concluded that military expenditure depends on a number of factors including: the nature of the expenditure; the prevailing circumstances; and the concurrent government policies.…”
Section: Policy Implicationssupporting
confidence: 90%
“…26, No. 3, 311-326, http://dx.doi.org/10.1080/10242694.2013.810024 Ó 2013Taylor & Francis 2007, the use of different sample periods (Chowdhury, 1991;Kusi, 1994) or the employment of different assumptions based on different theoretical models (Dunne, Smith, and Willenbockel, 2005); an aspect which is also related to the potential omission of relevant variables (Lai, Huang, and Yang, 2005;Bo and Xing, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Proponents of this school point that higher defense spending causes economic growth, and economic growth leads to higher ME (Cappelen, Gleditsch, & Bjerkholt, 1985) and (Kusi, 1994). This result is also confirmed by Chowdhury (1991) and Looney (1992).…”
Section: The Relationship Between Me and Economic Growthmentioning
confidence: 76%